PENERAPAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH (SPIP) DALAM PERSPEKTIF ‘’COSO’’ DI DESA KALIKURMO KECAMATAN BRINGIN KABUPATEN SEMARANG - HERNINDA PITALOKA; HENI WIDAYANTI; ANAVA SALSA N.S; MUTOHAR; NUR KABIB (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this study was to determine the effectiveness of the implementation of the Internal Control System in accordance with the Government Internal Control System (SPIP) in the Kalikurmo Village, Bringin District, Semarang. The method used is descriptive qualitative with primary data derived from interviews and documentation. The results showed that the Internal Control System was quite effective and in accordance with the Government’s Internal Control System (SPIP), but there were some things that had not been achieved, so the implementation of the Internal Control System had not been fully met.